Salidroside: An Overview of Its Promising Potential and Diverse Applications - Keke Liang; Shuhe Ma; Kai Luo; Renjie Wang; Chenrong Xiao; Xianxie Zhang; Yue Gao; Maoxing Li (Pharmaceuticals)
Salidroside, a phenolic compound isolated from various Rhodiola plants, is the principal active constituent of Traditional Chinese Medicine known for its adaptogenic properties. Due to the challenging environment of Rhodiola species, such as high altitude, high radiation, drought, and hypoxia, the source of salidroside is scarce. However, numerous studies have shown that salidroside has a range of biological activities, including cardiovascular and central nervous system activity, and anti-hypoxia, anti-inflammatory, and anti-aging activities. Although previous studies have partially summarized the pharmacological effects of salidroside, the overall pharmacological effects have not been analyzed. Hence, this review will systematically summarize the isolation, purification, synthesis, derivatization, pharmacological activity, pharmacokinetics, clinical application, and safety of salidroside. It is expected to provide new insights for the further research and pharmaceutical development of salidroside.